Examining the impact of musculus palmaris longus on serve speed and on certain motoric properties in tennis players - M. Soyal; M. Kaya; N.M. Çelik (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose: The aim of this study is to examine the impacts of existence or absence of musculus palmaris longus (MPL) on serve speed and certain motoric properties in the tennis players. Material: In the study, 25 male volunteers participated, who are playing tennis at university level and in whom the existence of musculus palmaris longus was checked. The ages of volunteers, who participate in tennis activities under licenses, vary between 18 and 25 and they have no disability or illness in the upper extremity. The experimental group (n=7) is comprised of individuals, who do not have musculus palmaris longus, while the control group (n=18) is comprised of individuals having musculus palmaris longus. Results: The age averages of the groups participating in the study was 21, 89±2, 246 years old for the group with musculus palmaris longus, while it was 22, 00±2, 517 years old for the participants without the musculus palmaris longus; as per their average height, it was 174, 94±5, 713 cm for the group with the musculus palmaris longus, while it was 174, 71±3, 546 cm for the participants without the musculus palmaris longus; the body weight average was 70, 83±5, 79 kg for the participants with musculus palmaris longus, while it was 72, 14±4, 059 kg for the participants without the musculus palmaris longus; sports-age average was 13, 00±1, 645 years for the ones with musculus palmaris longus, while it was 12, 29±1, 380 years for the participants without musculus palmaris longus. It was determined that there was statistically significant difference for the serve speed (p<0, 001) and the hand flexion strength (p<0, 05) parameters of the participants; however, there was statistically no significant difference (p>0, 05) in other parameters. Conclusions: As the conclusion, existence of musculus palmaris longus in tennis players positively influences the hand wrist flexion strength, however, it negatively influences the serve speed.